Targeting a Targeted Drug: An Approach Toward Hypoxia-Activatable Tyrosine Kinase Inhibitor Prodrugs - Karnthaler-Benbakka, Claudia (ChemMedChem, 2016)
Tyrosine kinase inhibitors (TKIs), which have revolutionized cancer therapy over the past 15 years, are limited in their clinical application due to serious side effects. Therefore, we converted two approved TKIs (sunitinib and erlotinib) into 2-nitroimidazole-based hypoxia-activatable prodrugs. Kinetics studies showed very different stabilities over 24 h; however, fast reductive activation via E. coli nitroreductase could be confirmed for both panels. The anticancer activity and signaling inhibition of the compounds against various human cancer cell lines were evaluated in cell culture. These data, together with molecular docking simulations, revealed distinct differences in the impact of structural modifications on drug binding to the enzymes: whereas the catalytic pocket of the epidermal growth factor receptor (EGFR) accepted all new erlotinib derivatives, the vascular endothelial growth factor receptor (VEGFR)-inhibitory potential in the case of the sunitinib prodrugs was dramatically diminished by derivatization. In line, hypoxia dependency of ERK signaling inhibition was observed with the sunitinib prodrugs, while oxygen levels had no impact on the activity of the erlotinib derivatives. Overall, proof of principle could be shown for this concept, and the results obtained are an important basis for the future development of tyrosine kinase inhibitor prodrugs.